PENGARUHINVENTORY TURNOVER TERHADAPRETURN ON ASSETSPADA PT. INDOFOOD CBPSUKSES MAKMUR, Tbk TAHUN 2011-2015 - Desta Agustina; Luis Marnisah; Endah Dewi Purnamasari (Jurnal Ilmiah Ekonomi Global Masa Kini)
The study aim the of was to find out the effect of Inventory Turnover on Return On Assets at PT. Indofood CBP Sukses Makmur Tbk. In this study, Inventory Turnover was considered variable and Return On Assets was dependent variable. The type of data used in this study was quantitative and the data source used was secondary. In collecting the data, documentation and biblio graphy were used. The data of the study was analized by calculating Inventory Turnover and Return On Assets, comparing Inventory Turnover and Return On Assets, the last five years in the quarter, that Inventory Turnover PT. Indofood CBP Sukses Makmur, Tbk 2011-2015 period experienced fluctuation, caused by sales and inventory that also experienced fluctuation. Inventory Turnover rotates one to three laps, meaning that the company is able to effectively manage the Inventory Turnover. Return On Assets (ROA) PT. Indofood CBP Sukses Makmur Tbk period 2011-2015 has fluctuated due to net profit and increase of total asset that also fluctuated.Every increase Inventory Turnover then Return On Assets will increase. Using simple regression analysis, Determination Cooficient (R square), and t-test. By sed on the simple linear reqression equation. It showed that the Inventory Turnover had a positive effect on the Return On Assets. In addition, the result of t-test also showed that Inventory Turnover had a significant effect on Return On Assets.Keywords:Inventory Turnover, Return On Assets, financial performance